Infarction of the central cerebellar arbor vitae and transient loss of spatial orientation - Sedlaczek, Oliver; Grips, Eva; Bäzner, Hansjörg; Claus, Alexandra; Wöhrle, Johannes C.; Hennerici, Michael G. (Neurology, 2005)
A 45-year-old man traveling by train had acute severe pain in the right shoulder after lifting a heavy suitcase, followed by 15 seconds of non-motion-directed vertigo. He sat down and felt well, except for minor persisting pain in the shoulder. After a symptom-free interval of 4 hours, he reported a sudden transient loss of spatial orientation and a feeling of being shaken in an airplane during severe turbulence. Apparently he had involuntarily moved on his seat, prompting startled looks from fellow passengers. During this episode, he had no diplopia, nausea, or visual disturbances. After a few minutes, he recovered completely apart from persisting pain in the right shoulder and neck. Orthopedic consultation and …
Gesehen am 26.03.2021